STRATEGI PENANGANAN BERCAK DAUN CURVULARIA SP. PADA PEMBIBITAN KELAPA SAWIT DI INDONESIA - Irham, Wardatul Husna; Saragih, Sri Wahyuna; Febrianto, Eka Bobby; Yazid, Abu; Haholongan, Rahmat; Maulana, Andre; Damanik, Riski (Agro Estate, 2023)
Oil palm (Elaeis guineensis Jacq) is one of the plantation crops that produces vegetable oil which has become the main ingredient and leading agricultural commodity in Indonesia. The quality of oil palm seedlings is a disease attack during the seedling stage. The most common disease found in oil palm nurseries is leaf spot disease. The aim of this research is to propose strategies for handling leaf spot in oil palm nurseries in Indonesia. This research is a literature study research. The data used comes from secondary data. Data collection methods use textbooks, journals and periodical. Data analysis is carried out by reading, collecting, citing information, concluding and interpreting the results obtained through relevant study materials. The results obtained that there are several strategies that can be used to treat leaf spot in oil palm nurseries in Indonesia, i.e. by carrying out photon energy irradiation which can increase plant resistance to various types of pathogens, developing organic fertilizer formulations and using biocontrol agent which is expected to help oil palm nurseries in suppressing leaf spot disease, using fungicides to prevent resistance, taking preventive measures to reduce the risk of spot disease on oil palm leaves, carrying out conservation fertilization using S2 (385 mesh), S3 (638 mesh), and S4 (644 mesh) sachets and applying liquid  smoke areca nut in suppressing the growth of Curvularia sp.